Monitoring of school wellness based on the effect of volleyball methodology (Research Announcements "Heritage BG", 2025)
Objective: The study aims to establish the effect of the innovative volleyball methodology and its influence on the motor development level of volleyball players actively practicing this approach. Methods: The research aims to establish the reasons for the change in the biomechanical motor indicators as a result of the applied volleyball methodology, based on benchmarking the biomechanical parameters to determine the effect of the volleyball methodology on the degree of development of the motor qualities. The study contingent consisted of 26 7th-grade girls aged 13-14, practicing volleyball at a metropolitan school. The present study was conducted during the 2023-24 school year. Results: The subject of research is the dynamics of biometric indicators in one school year. Discussion: Motor activity measurements were performed at the beginning of the study, before the implementation of the innovative volleyball methodology, and at the end after the implementation. Conclusion: The influence of active sports on the motor development of volleyball players has undoubtedly been established. Analyzing the research from the conducted diagnostics, during the study a comparative analysis of the biomechanical motor indicators in two cognitive stages of the studied period was carried out to establish the effect of the applied volleyball methodology.
Keywords: Benchmarking analysis; biomechanical parameters; volleyball methodology